On-chip synthesis of fine-tuned bone-seeking hybrid nanoparticles. (December 2015) - Hasani-Sadrabadi, Mohammad Mahdi; Dashtimoghadam, Erfan; Bahlakeh, Ghasem; Majedi, Fatemeh S; Keshvari, Hamid; Van Dersarl, Jules J; Bertsch, Arnaud; Panahifar, Arash; Renaud, Philippe; Tayebi, Lobat; Mahmoudi, Morteza; Jacob, Karl I
Aims: Here we report a one-step approach for reproducible synthesis of finely tuned targeting multifunctional hybrid nanoparticles (HNPs).Materials & methods: A microfluidic-assisted method was employed for controlled nanoprecipitation of bisphosphonate-conjugated poly(D, L-lactide-co-glycolide) chains, while coencapsulating superparamagnetic iron oxide nanoparticles and the anticancer drug Paclitaxel.Results: Smaller and more compact HNPs with narrower size distribution and higher drug loading were obtained at microfluidic rapid mixing regimen compared with the conventional bulk method. The HNPs were shown to have a strong affinity for hydroxyapatite, as demonstrated in vitro bone-binding assay, which was further supported by molecular dynamics simulation results. In vivo proof of concept study verified the prolonged circulation of targeted microfluidic HNPs. Biodistribution as well as noninvasive bioimaging experiments showed high tumor localization and suppression of targeted HNPs to the bone metastatic tumor.Conclusion: The hybrid bone-targeting nanoparticles with adjustable characteristics can be considered as promising nanoplatforms for various theragnostic applications.